Computational Analysis of Surface Plasmon Resonance - Mokhtar, Rosmiza (2008)
The Surface Plasmon Resonance (SPR) technique was used as a sensitive optical sensor as well as characterizing materials. To achieve these, two computer programs were developed to carry out an accurate curve fitting of theory to reflectivity data. Two programs were developed preceding from the following requirement that SPR technique can be carried out by using two configurations. The first configuration was the prism coupling, where the program was developed based on the Fresnel’s Equations. The second configuration was the grating coupling, where the program was developed based on the coordinate-transformation-based differential method of Chandezon et al. (1980) (the C Method). The fitting process was done by adjusting the relevant parameters (i.e., thickness and dielectric constants) until the lowest sum of square error was obtained. In order to know whether the results from the developed computer program represent the real situation, we have examined our program with the experimental results carried out by other researchers. We have achieved a satisfactory agreement. Furthermore, surface plasmon resonance simulations on single and multilayer were presented to motivate an effort to understand the shape of the resonances when a surface was exposed to the environment filled with toxic gas. The film growth due to the exposition was studied by understanding the effect of increasing thickness and also the modification of effective permittivity. We also investigated the effect on surface plasmon resonance by varying the grating period and grating profile. We achieved an excellent understanding of the shape of reflectivity curve when the optical constants of layers, the grating period and grating profile, were varied, for both prism coupling and grating coupling, respectively. In the SPR measurement, the angle of resonance is very sensitive to any surface layer over a metal thin film. The existence of extremely thin surface layer can cause a detectable shift of the SPR curve, which indicates the sensitivity of resonance angle to the changes in the environment of the metal layer. In the present work, SPR technique was used as a tool for the detection of toxic gases, i.e. hydrogen sulfide (H2S) gas and carbon monoxide (CO) gas. The gold-coated prism was used as a sensor head. The experiments were carried out by measuring the reflected intensity as a function of incident angle. By using the developed programs, the optical permittivity of the material was obtained giving an accurate characterization of the changes brought about by the H2S and CO gases. This is one of the important characteristics of constructing the optical gas sensor. We have theoretically modeled a surface plasmon resonance device that is sensitive to both the refractive index and thickness of an adsorbed film. An extensive numerical simulation of the sensor is performed using the scattering matrix approach. The method is capable of monitoring environmental changes in a wide range of applications. With further effort and modification, we believe it is possible to expand the functionality of the surface plasmon resonance sensor to provide powerful tools for the determinations of optical constant of materials and also the determination of grating profiles and grating period. Some of the limitations and breakdowns may also be fixed in the future.